Ageing prisoners: An introduction to geriatric health-care challenges in correctional facilities. (17th November 2017) - Bedard, Rachael; Metzger, Lia; Williams, Brie
Abstract: The rise in the number of older prisoners in many nations has been described as a correctional "ageing crisis" which poses an urgent financial, medical and programmatic challenge for correctional health-care systems. In 2016, the International Committee of the Red Cross hosted a conference entitled "Ageing and Imprisonment: Identifying the Needs of Older Prisoners" to discuss the institutional, legal and health-care needs of incarcerated older adults, and the approaches some correctional facilities have taken to meeting these needs. This article describes some of the challenges facing correctional systems tasked with providing health care to older adults, highlights some strategies to improve their medical care, and identifies areas in need of reform. It draws principally on research and examples from the United States to offer insights and recommendations that may be considered in other systems as well.